Great scientists - Fortey, Jacqueline (London ; New York : DK, 2007)
Full-color illustrations and photographs introduce readers to the great scientists and their discoveries from ancient history to modern times. Includes clip-art CD-ROM and wall chart.
Includes index.
Keywords: Scientists -- Juvenile literature; Science -- Juvenile literature